Effect of sudden change in potassium concentration on Penaeus latisulcatus Kishinouye survival, osmolality and health in inland saline water cultures - Prangnell, David; Fotedar, Ravi (Springer, 2009)
The aim of the project was to determine the effects of sudden change in potassium concentration in inland saline water on the survival, osmolality and condition indices of western Australian King Prawn - Penaeus latisulcatus Kishinouye. Australia has large volumes of inland saline water that could be used for aquaculture but is often deficient in K+. Western king prawn is a candidate species for culture in inland saline water. Such waters require K+ fortification for prawn survival and growth. Trials were conducted in tanks to determine the effect of sudden change in K+ concentration in inland saline water samples on the survival, osmolality and condition indices of western king prawns. Prawns in tanks were acclimated to inland saline water procured from Wannamal- an inland location in Western Australia. After 3 days of acclimation, prawns were subjected to sudden increase in medium K+ concentration over 1 h, ranging from 80% to 100% of the marine water K+ concentration by adding potassium chloride. Identical inland saline water was added to the control tanks over the same time period. Survival, ingestion rate and osmoregulatory capacity (OC) were then recorded over 19 days. At the conclusion of the trial, survival ranged from 71% to 78% in the potassium-enriched tanks whereas 100% mortality was observed in the control tanks by day 11. Ingestion rate of prawns was significantly higher in the experimental tanks than in the control. Osmoregulatory capacity of potassium-enriched prawns was significantly lower post- than pre-ionic change and significantly higher at the conclusion of the trial than both pre- and postionic change. There was no significant difference in OC between water types at any time period. These results indicate that prawns can tolerate sudden increase in K+ content in inland saline water and the higher K+ concentration increases survival and OC, but other measures indicate the prawns were experiencing stressful conditions.